The Relationship Between Nutritional Status Of Toddlers And Family Smoking Behavior With The Imcidence Of Pneumonia In Toddlers In The Working Area Of Candi Public Health Center - Agustine, Nita Claudia; Loetfia Dwi Rahariyani; Kusmini Suprihatin; Suprianto (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2025)
Pneumonia is the most prevalent and possibly fatal respiratory illness among children under five. The purpose of this study is to look at the connection between family smoking habits, nutritional status, and the prevalence of pneumonia in children under five in the Candi Health Center's working region. 43 families with children ages 0 days to under 5 years who sought treatment at the Candi Health Center were chosen using the sequential sampling technique. This study employs descriptive analysis and a cross-sectional methodology. 86% of participants in the research had acceptable nutritional status. Furthermore, according to 80% of families, at least one person smokes at home. Bivariate analysis using the Chi-Square Test revealed no significant correlation between the incidence of pneumonia and baby nutritional health (p=0.190); nevertheless, there was a high correlation between the incidence of pneumonia in infants and family smoking (p=0.000). Toddlers' health is negatively impacted by family smoking practices, particularly because it raises their risk of pneumonia. Families with small children should know how important it is to keep smoking away from them, safeguard their health, and take them to the doctor on a regular basis for exams.